Growing Pains, Evolution and Progress - Paz-Pacheco, Elizabeth (Journal of the ASEAN Federation of Endocrine Societies, 2014)
Six issues over the last three years saw JAFES undergo a remarkable transformation—from a journal with humble operations in the heart of Manila—to a publication that dares to be noticeable by the world. Since 2013, we have shifted to Open Access and made all articles published from 2011 to the present available online for download in portable document formats, without charging any manuscript processing fees to authors. This year, through the Open Journal Systems of the US Public Knowledge Project, we shall be launching the new JAFES website platform with electronic journal management